STANDARDIZATION OF IN HOUSE PREPARED POLYHERBAL FORMULATION RAJA PRAVARTINI CHURNA - Kumar Baranwal, *Harsh; Kumar, Ashish; Ruhela, Kajal; Nainwal, Pankaj (International Journal of Ayurveda and Pharma Research, 2018)
The present study is to set up and check the standardization parameter for a poly-herbal formulation Raja Pravartini Churna. The marketed formulation and in house prepared formulation with same formula is taken for study. The parameter for standardization are organoleptic character, loss on drying, bulk density, tapped density, angle of repose, carr’s index, husner’s ratio, florescence analysis, powder microscopy, Phytochemical screening, ash values, extractive values etc were evaluated during the study on both formulation. The set parameters were found to be sufficient to standardize the Raja Pravartini Churna and can be used as reference standards for the quality control/ quality assurance study mostly on plant drugs for their primary health care needs.